2000
DOI: 10.1038/sj.onc.1203422
|View full text |Cite
|
Sign up to set email alerts
|

RAFTK/Pyk2 tyrosine kinase mediates the association of p190 RhoGAP with RasGAP and is involved in breast cancer cell invasion

Abstract: Focal adhesions and actin cytoskeleton are involved in cell growth, shape and movement and in tumor invasion. Mitogen-induced changes in actin cytoskeleton are accompanied by changes in the tyrosine phosphorylation of several focal adhesion proteins. In this study, we have investigated the role of RAFTK, a cytoplasmic tyrosine kinase related to focal adhesion kinase (FAK), in heregulin-mediated signal transduction in breast cancer cells. Stimulation of T47D cells with heregulin (HRG) induced the tyrosine phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 49 publications
3
68
1
Order By: Relevance
“…We propose that in androgenindependent, AR-positive PCa cells, ErbB-2 protein is constitutively activated and/or elevated as seen in clinical samples due, in part, to the loss or null of cPAcP expression (Signoretti et al, 2000;Veeramani et al, 2005). In those advanced PCa cells, signal pathways initiated by highly activated ErbB-2 lead to a sustained activation of PYK2 and PYK2-mediated functions, which differs from the transient effect activated by ErbB ligands (Zrihan-Licht et al, 2000;van der Horst et al, 2005;Park et al, 2006). Further investigation for the detailed molecular mechanism of ErbB-2 activation is required.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We propose that in androgenindependent, AR-positive PCa cells, ErbB-2 protein is constitutively activated and/or elevated as seen in clinical samples due, in part, to the loss or null of cPAcP expression (Signoretti et al, 2000;Veeramani et al, 2005). In those advanced PCa cells, signal pathways initiated by highly activated ErbB-2 lead to a sustained activation of PYK2 and PYK2-mediated functions, which differs from the transient effect activated by ErbB ligands (Zrihan-Licht et al, 2000;van der Horst et al, 2005;Park et al, 2006). Further investigation for the detailed molecular mechanism of ErbB-2 activation is required.…”
Section: Discussionmentioning
confidence: 97%
“…Since both high passages of LNCaP C-81 and MDA PCa2b cells had higher levels of ErbB-2/PYK2 functional complexes than corresponding low passage cells, it suggested that the association of ErbB-2 with PYK2 in the same complex is critical for PYK2 activation and its regulation of cell adhesion. Although c-Src may serve as a mediator for ErbB-2/PYK2 interaction in 293T cells (Zrihan-Licht et al, 2000), inhibition of c-Src in C-81 cells has no effect on PYK2 activity and the initial adhesion (Supplementary Figure 3B). Further, the K457A-PYK2 mutant can still activate c-Src, while it inhibits ErbB-2-promoted adhesion ( Figure 6, Supplementary Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAK is also important in integrin-mediated cell cycle progression through the mitogen activating protein (MAP) kinase pathway [74,75]. Additionally, FAK and Pyk2 activation are implicated in the growth and metastasis of transformed cells [76][77][78]. Together, these data imply that FAK is an important intersection point for cell motility and growth transformation.…”
Section: Focal Adhesion Kinases (Faks) and Chemokine Signalingmentioning
confidence: 99%
“…SH domains of p120-GAP function as effectors by associating with several tyrosine-phosphorylated proteins [5], which induce Ras-dependent gene expression [6] and repress adhesion [7]. In addition, p120-GAP is involved in Ras transformation [8,9], cell survival [10,11,12] tumor cell invasion [13], and v-Src-induced cytoskeletal disruption [14]. Based on these findings, p120-GAP proteins show promise as a target for anticancer approaches [11].…”
Section: Introductionmentioning
confidence: 99%